Biogeochemical responses to internal-wave impacts in the continental margin off Dongsha Atoll in the Northern South China Sea. (December 2021) - Hung, J.-J.; Wang, Y.-H.; Fu, K.-H.; Lee, I-H.; Tsai, S.-S.; Lee, C.-Y.; Lu, W.-T.; Shen, Y.-J.; Lin, Y.-H.
Highlights: Depressed and elevated waves modulate nutrient and carbon fluxes in the margin. Shoaling causes cooler and nutrient-rich waters that enhance surface POC fluxes. Depressed waves mediate vertical transfer of surface-dissolved gases and materials. Shoaling benefits balance countereffects of uplifted low-pH DO waters in the shelf. Shoaling may positively affect the health of Dongsha Atoll-related coral ecosystems. Abstract: This study aimed to understand the effects of nonlinear internal waves (NLIWs) on nutrient-involved biogeochemical processes and the consequences in the continental margin off Dongsha Atoll (DA) in the northern South China Sea (NSCS). Shipboard and mooring observations were conducted to determine hydrological and biogeochemical conditions mainly from two transects covering the DA-associated upper slope, shelf break, and shelf zones. A dense array of thermistor moorings and a temperature-fluorescence-sediment trap array were deployed on the same transect to determine the short-period variability of transport and shoaling of NLIWs across the shelf and to link physical variability to biogeochemical consequences induced by NLIW events. The shoaling of NLIWs appeared to uplift cooler and nutrient-rich subsurface water into the nutrient-deplete surface in shelf and nearshore environments as well as increase nutrient concentrations and biological production. We observed shoaling events that induced a notable range of upward fluxes in nitrate and nitrite (0.42–2.92 mmol N m −2 d −1 ) onto the euphotic zone to enhance and sustain new production, depending on the strength of shoaling activity in various observations. The shoaling-derived new production may fully elucidate the amount of sinking fluxes of particulate organic carbon measured from the shoaling field. According to short-time sequential observations during the passage of a single NLIW, the depressed waves may play a crucial role in enhancing the vertical transfers of surface-replete dissolved gases, carbon, or suspended constituents through the surface layers of stratified waters. This NLIW forcing appears to be effective in supplying cooler and nutrient-rich water to the DA-associated coral community, and this may be vital for improving the future development and conservation of the coral ecosystem.